Design of U and I Ferrite Core On Dynamic Wirelesss Charging for Electric Vehicle - Abdullah, Amira Aziera; Yusoff, Siti Hajar; Sulaiman, Erwan; Midi, Nur Shahida; Badawi, Ahmed Samir Abed; Fakhruddin, Anis Farihah (IEEE, 2021)
This study provides an approach investigation of U and I ferrite core geometrics to improve the power efficiency for Electric Vehicle (EV) inductive wireless charging in dynamic mode. Dynamic wireless charging (DWC) enables recharging of battery pad during the vehicle is on the road. Hence, the design of battery pad must deal with two main factor that led to power leakage such air gap and misalignment. Using ferrite magnetic core, it improves the power transferred by reduce the leakage magnetic radiation between primary and secondary side. Different conditions are investigated on U and I core. The first and second condition is U or I core only at primary side and secondary U or I core only at the secondary side. The last condition is both at primary and secondary side of U or I ferrite core. The purpose of this project is to design a prototype of EV thru several method, design proposed, circuit simulation, pair simulation and prototype development. NI Multisim are used to simulate circuit of WPT for operation validity.